Strengthening mechanism and electrochemical characterization of ZrO2 nanoparticles in Nickel-Aluminum alloy for Molten Carbonate Fuel Cells - Frattini, Domenico; Accardo, Grazia; Moreno, Angelo; Yoon, Sung Pil; Han, Jong Hee; Nam, Suk Woo (한국공업화학회, 2017)
In this work the positive effect of zirconia nanoparticles in Nickel-Aluminum anodes is investigated: Results showed that, as the zirconia content increases, bending strength and creep resistance are improved. Mechanical strength increases from 5.94 to 11.38 kg(f) cm(-2) and creep is reduced up to 3.31%. Morphology and microstructural analysis revealed that nanoparticles adhere strongly on the surface of larger metal particles and microstructure is strengthened at grain level. The diffusion of Aluminum atoms into different vacancies reduces dislocations movement. A part these mechanisms, charge and mass transfer resistance are lower and the internal resistance after 500 h at 650 degrees C is 0.24 m Omega cm(2). (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.